To solve \(-1 \frac{3}{10} + (-4 \frac{2}{15})\), we first convert the mixed numbers into improper fractions.
-
Convert \(-1 \frac{3}{10}\) to an improper fraction: \[ -1 \frac{3}{10} = -\left(\frac{1 \times 10 + 3}{10}\right) = -\left(\frac{10 + 3}{10}\right) = -\frac{13}{10} \]
-
Convert \(-4 \frac{2}{15}\) to an improper fraction: \[ -4 \frac{2}{15} = -\left(\frac{4 \times 15 + 2}{15}\right) = -\left(\frac{60 + 2}{15}\right) = -\frac{62}{15} \]
Now, we need to add \(-\frac{13}{10} + -\frac{62}{15}\).
-
To add these fractions, we need a common denominator. The least common multiple (LCM) of 10 and 15 is 30.
-
Convert \(-\frac{13}{10}\) to have a denominator of 30: \[ -\frac{13}{10} = -\frac{13 \times 3}{10 \times 3} = -\frac{39}{30} \]
-
Convert \(-\frac{62}{15}\) to have a denominator of 30: \[ -\frac{62}{15} = -\frac{62 \times 2}{15 \times 2} = -\frac{124}{30} \]
Now we can add the two fractions: \[ -\frac{39}{30} + -\frac{124}{30} = -\frac{39 + 124}{30} = -\frac{163}{30} \]
- Now we can convert \(-\frac{163}{30}\) into a mixed number: \[ -\frac{163}{30} = -5 \frac{13}{30} \quad \text{(since 163 divided by 30 is 5 remainder 13)} \]
Thus, the result is \(-5 \frac{13}{30}\).
Therefore, the final answer is: D. -5 \frac{13}{30}.